Type and abundance of phytoperiphyton in the plastic substrate placed in the Bunter Lake, Pangkalan Baru Village,Siak Hulu Sub-districts, Kampar Districts, Riau Province - Annisa Amaliah; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPhytoperiphyton is a microscopic organism that attach on certain substrate. Research aims to determine the type and abundance of phytoperiphyton on plastic substrate has been carried out in June- July 2019 in the Bunter Lake. There were three sampling stations, namely Station 1 (inlet), Station 2 (in the middle of the lake) and Station 3 (in the end of the lake ). The number of substrates in each station were 30 pieces. Sampling were conducted once/week for a 3 weeks period. The phytoperiphyton samples are brushed from the plastic substrate (8x3 cm),  10  plastic substrates/ stations. Water samples were collected from 2 different depth namely in the surface (20 cm) and 2 secchi depth (180 cm). Water quality parameters measured were temperature, transparancy, pH, dissolved oxygen, free carbon dioxide, nitrate and phosphate. Results shown that there were 28 types of phytoperiphyton present and they were belonged to 3 classes, namely  Chlorophyceae (15 species), Bacillariophyceae (10 species), and Cyanophyceae (3 species). The abundance of phytoperiphyton were 8,236- 19,581 cells/cm2. The water quality parameters were as follows: temperature was 29.7-30oC, transparancy was 78.33- 83.67 cm, dissolved oxygen was4.07-6.13 mg/L, pH was 5, free carbon dioxide was 7.32-13.31 mg/L, nitrate was 0.05413-0.10267 mg/L and phosphate was0.02137-0.03983 mg/L. Based on type of phytoperiphyton, trophic state of  Bunter Lake can be categorized as eutrophic.Keywords : Lentic, Sessile Organism, Water Quality, Trophic State,Oxbow Lake